Enhancement of fibroblastic proliferation from photoreactive starch with immobilized epidermal growth factor. Issue 4 (15th January 2013) - Cho, Young‐Min; Lee, Hyung‐Jae; Heo, Yun; Park, Shin‐Hye; Seo, Si‐Yoong; Han, Jae‐Hong; Son, Tae‐Il
Abstract Carboxymethyl starch was modified by the incorporation of an azidophenyl group to prepare photoreactive starch, and characterized by Fourier transform infrared reflectance (FT‐IR), proton nuclear magnetic resonance (1H‐NMR), and ultraviolet (UV) spectroscopy. Photo‐irradiation immobilized the Az‐starch on a polystyrene plate and it was stably retained on the surface. The protein containing immobilized Az‐starch was also immobilized on a stripe micropatterned plate. UV irradiation time and Az‐starch concentration were used to alter the physical properties of Az‐starch and consequently control the rate of epidermal growth factor (EGF) release. The Az‐starch that released growth factor was not cytotoxic to 3T3‐L1 fibroblast cells, and the immobilized EGF maintained its activity and induced cellular proliferation in vitro. These results suggest that Az‐starch could be useful as a clinical synthetic material for medical applications. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013